Subjective Age and Psychological Well-Being - E.A. Sergienko; N.S. Pavlova (Современная зарубежная психология, 2025)
The article deals with the role of a person's subjective age in his psychological well-being. Subjective age is the self—perception of one's own age, it’s a subjective age identification. Foreign and domestic studies convincingly show the predictive role of subjective age in life expectancy, somatic health, regulation of vital activity; countering stress and post-stress disorders, as well. Subjective age becomes an intuitive assessment of a person's own resources, possibilities of their reorganization and integration in threatening situations. This is a flexible psychological mechanism for regulating vital activity. Subjective age is considered as a predictor of successful aging, which is important not only for psychology, but also for economics and social policy. The question of the interrelationship between a person's subjective age and indicators of his psychological well-being remains open. Many scientific papers point to the importance of psychological factors, including subjective age, for psychological well-being. At the same time, several longitudinal studies suggest the opposite: health and well-being may be prerequisites for subjective age.